The role of highway construction in influencing agricultural green total factor productivity in China: agricultural industry structure transformation perspective - Zhou, Zhou; Duan, Jianqiang; Geng, Shaoqing; Li, Ran (Frontiers in Sustainable Food Systems, 2024)
Highway construction is vital in agricultural production, directly influencing food security and public health. This study utilized the Epsilon-based measurement-global-Malmquist-model (EBM-GML) and the spatial econometrics model with 31 Chinese provinces’ panel data from 2002 to 2020 to investigate the impacts and the mechanisms of low-grade and high-grade highways on the agricultural green total factor productivity (AGTFP). Research findings indicated that (1) low-grade and high-grade highway construction significantly promote the AGTFP through technological progress, and the high-grade highway exerts a significant positive spillover effect on the adjacent areas’ AGTFP. (2) The mechanisms of low-grade and high-grade roads on the AGTFP are heterogenous. Low-grade roads could improve the AGTFP by encouraging the rationalization of the agricultural industry structure. High-grade highways promote the AGTFP by upgrading the industry structure. And each-grade road could promote the AGTFP by stimulating the integration of planting and breeding. (3) Both low-grade and high-grade highways improved the AGTFP in non-main-grain-producing areas but inhibited it in main-grain-producing areas. Therefore, this study provided practical policy recommendations for green development in China’s agricultural sector and valuable insights for other developing countries.